Molecular Phylogeny of Indonesian Armyworm Mythimna Guenée (Lepidoptera: Noctuidae: Hadeninae) Based on CO I Gene Sequences - HARI SUTRISNO (HAYATI Journal of Biosciences, 2012)
Armyworm Mythimna Guenée is one of the most important pests on graminaceous crops and pastures in South East Asia (i.e. M. separata Walker is well known to cause serious damages on rice in Indonesia). Like of most other genera of moths, the systematic of this genus is still in dispute, especially on the taxonomy and classification within this genus due to their morphological characters that are very difficult to distinguish from one to others. Molecular approaches such as using CO I gene sequence to differentiate among species has been recommended since this gene has ability to reveal the character identity at the specific level.  In order to populate the genetic characters of Indonesian Mythimna, to clarify the clasification within the genus Mythimna and to reveal the phylogenetic relationship among them, we analyzed 14 species of Mythimna and two species outgroups (Spodoptera litura dan S. exigua) based on nucleotide sequence variation across a 649 bp region in the CO I gene.  Over entire 649 bp region 72% of the nucleotide positions were constant, 10.6% were uninformtive (i.e. any variants were found in a single sequence) and 16.9% were parsimony informative. The informative site constituted in the 3rd codon position was the highest, whereas in 2nd codon position was the lowest. The results also showed that the base composition of this region was low A + T biased. The results showed that the monophyly of Mytimna was supported by 95% bootstrap test at any tree building methods. The three subgenera based on morphology were recovered but M. (Mythimna) shown to be a paraphyletic group in term of M. (Hyphilare), and M. (Pseudalteia); M. (Mythimna) was branched off first then followed by M. (Pseudaletia) and M. (Hyphilare).  However, all internal nodes were least support except for the monophyly of subgenus M. (Hyphilare). It indicates that the relationships among internal nodes proposed here were least valid due to the number of species included in the analysis which may not be enough to represent the real number of species in the nature. More investigation was needed by including more species and other genes.